The Embeddedness of Traditional Economy Transforming Towards An Alternative Economy: A Case Study of Lumbung Pitih Nagari (LPN) Limau Manis, West Sumatra - Rahmaini, Indah Sari; Sujito, Arie (Masyarakat: Jurnal Sosiologi, 2021)
This article seeks to observe the modernization of economic institutions that were originally working traditionally, into alternative economic institutions that continue to apply the value of locality. Previous studies on LPN Limau Manis only discussed its role in poverty alleviation and the management of its economic organization, but did not provide a comprehensive explanation of the transformation of LPN that combines traditional and modern concepts. This article argues that the institutional modernization of LPN Limau Manis that occurs remains attached to the customary values of the Nagari society. The qualitative method was used to collect data using a case study research. This article revealed that the LPN, which underwent a transformation into a modern management system, remained attached to the social conditions of Nagari society as seen from the social profit-based approach. However, the transformation of LPN to an alternative economy also shows an element of local capitalism that